SEED PRODUCTION IN OKRA (ABELMOSCHUS ESCULENTUS (L.) MOENCH) (1987)
Fifteen genotypes of okra were evaluated in eight environments for stability of seed yield, and also to identify the most suitable environments for producing high quality seed at the University of Ibadan, Nigeria from 1984 to 1986. There was significant genotype x environment interactions for all characters examined except for percent seed germination. On the average, highest seed yield and best seed quality as measured by percent seed germination were associated with environments with low total precipitation (460.4 mm), low average relative humidity (50.1%) and high number of sunshine hours (1153.7 hrs). Studies on agronomic requirements for okra seed production revealed that high plant population (111,110 plants/ha) produced about 39% higher seed yields/ha than low plant population of 55,555 plants/ha. Nitrogen levels of 65 kg/ha and 130 kg/ha raised seed yield by 35 and 39% over the control (no nitrogen) respectively. Seeds harvested 35-49 DAF, stored in polythene bags at 4°C with 50% RH retained most of their viability after 16 months of storage. Removing the first two to four edible pods on each plant raised okra seed yields by about three percent. Removal of the first 6 to 14 pods/plant reduced seed yields by 36-80%. Removal of up to four edible pods/ plant was compensated for by higher total pod dry matter yield reflected in a higher 1000-seed weight and larger size of seeds. Seeds in categories of 4.0 and 4.5 mm size grades were more vigorous as indicated by 1000-seed weight, percent seed germination and seedling emergence.